2020
DOI: 10.1186/s12870-020-02690-z
|View full text |Cite
|
Sign up to set email alerts
|

The Nicotiana tabacum L. major latex protein-like protein 423 (NtMLP423) positively regulates drought tolerance by ABA-dependent pathway

Abstract: Background Drought stress is an environmental factor that limits plant growth and reproduction. Little research has been conducted to investigate the MLP gene in tobacco. Here, NtMLP423 was isolated and identified, and its role in drought stress was studied. Results Overexpression of NtMLP423 improved tolerance to drought stress in tobacco, as determined by physiological analyses of water loss efficiency, reactive oxygen species leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Plants have evolved a range of regulatory mechanisms to cope in response to environmental stresses, for example, osmotic regulation, antioxidant defense regulation, signal transduction mechanisms, etc. The abscisic acid (ABA) signaling pathway plays an important part in the response of plants to abiotic stresses ( Campos-Rivero et al., 2017 ; Liu et al., 2020 ). ABA regulates plant physiological and metabolic responses by controlling the expression levels of many stress-responsive genes, enabling plants to tolerate stresses ( Ma et al., 2018 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have evolved a range of regulatory mechanisms to cope in response to environmental stresses, for example, osmotic regulation, antioxidant defense regulation, signal transduction mechanisms, etc. The abscisic acid (ABA) signaling pathway plays an important part in the response of plants to abiotic stresses ( Campos-Rivero et al., 2017 ; Liu et al., 2020 ). ABA regulates plant physiological and metabolic responses by controlling the expression levels of many stress-responsive genes, enabling plants to tolerate stresses ( Ma et al., 2018 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that overexpression of the AtMLP43 gene can mediate ABA signaling to improve drought tolerance [31]. Overexpression in transgenic tobacco plants of the major latex-like protein gene NtMLP423 resulted in greater sensitivity to abscisic acid (ABA)-mediated seed germination and ABA-induced stomatal closure, and enhanced drought tolerance in tobacco by increasing ABA levels [32]. Based on this, we speculated that the expression of ABA-responsive genes might be altered in overexpressed plants.…”
Section: Discussionmentioning
confidence: 91%
“…When exposed to the osmotic adjustment substance PEG or a water deficit, overexpression lines showed greater tolerance to water stress and had significant plant heights, survival rates, and water retention statuses [43]. It was reported that overexpression in transgenic tobacco plants of the major latex-like protein gene NtMLP423 resulted in greater sensitivity to abscisic acid (ABA)-mediated seed germination and ABA-induced stomatal closure, and it enhanced drought tolerance in tobacco by increasing endogenous ABA levels [44]. Ectopic overexpression of the cotton GhMLP28 gene in Arabidopsis enhanced tolerance to salt stress [45].…”
Section: Discussionmentioning
confidence: 99%